Bário em soluções de nutrição parenteral e medicamentos: origem, níveis de contaminação e avaliação da distribuição no organismo em modelo animal - Mörschbächer, Vanessa Domingues (2012)
Barium (Ba) contamination in solution for parenteral nutrition (PN) and drugs was studied. The concentration of Ba was determined by F-AAS in glass and plastic packaging used to store the formulations, since the compounds of Ba can be used as material raw of these materials. PN and drugs administered to preterm infants in the neonatal Intensive Care Unit (ICN) of the Hospital of Federal University of Santa Maria (HUSM) were analyzed by GF-AAS. Glass containers, bottles and ampoules, showed from 4.1 mg/g to 4.9 mg/g of Ba. PVC bags and polyethylene bottles showed from 0.15 mg/g to 0.04 mg/g of Ba, respectively. In rubber stoppers were found between 0.02 mg/g and 0.04 mg/g of Ba, and 4.4 mg/g of Ba was measured in the plunger of the syringes. Commercial solutions of the constituents of PN, with exception of solutions of KCl and NaCl, showed Ba as a contaminant. The concentration ranged from 27 μg/L and 262 μg/L, and the most contaminated formulations were: vitamins, magnesium sulfate, calcium gluconate and amino acid pediatric. It was found that the PN solution prepared and stored in bags were more contaminated than would be expected for the contribution of each individual constituent. The fractions of PN solutions that remained in burettes, which is a device connected to the bag to help control volume to be administered, were more contaminated by Ba that their respective bags, concluding that the preparation and addition of drugs in the solutions in this compartment significantly increases the amount of Ba. The drugs studied showed no contamination by Ba. However, after dilution in syringes, concentration between 87 and 585 μg/L were found in samples of dexamethasone disodium phosphate, amikacin sulfate and gentamicin sulfate. As drugs stored in syringes remained in direct contact, for several days, with the rubber plungers, this must be the source of Ba in the analyzed drugs. Contact testing using an ion-exchange resin conditioned with Ba and solutions of constituents of the PN solutions and the drugs were performed to simulate the interaction of the compounds with Ba packaging. The test results showed that calcium gluconate and citric acid were the constituents of PN and drugs that interacted with Ba at most, removing greater amount of the metal form the resin. These results confirmed that the Ba can be removed from the packaging material into solutions by action of constituents of PN solutions. Experiments in animal model were carried out to verify the effect of Ba in the living organism when directly administered into the bloodstream, as it occurs in the administration of PN solutions. The lethal dose 50 (LD 50) of 9.6 mg/kg was determined for the BaCl2 in adult female Wister rats by intraperitoneal via due to the need to know a safe dosage to be administered in the study on the effect of Ba in organism and has not been consistent values in literature. After this study, adult male Wister rats were subjected to treatment with Ba combined or not with sodium citrate and calcium gluconate. Posteriorly 30 administrations the animals were sacrificed, then, samples of brain, heart, liver, kidney, muscle, bone and blood were collected. Several procedures for digestion of tissue were tested to suppress, as much as possible, the interference caused by matrix in determination of Ba by GF-AAS. The most suitable procedure which was digestion sample with 1 mL of HNO3 and analysis was carried out the standard addition calibration. The results of the administration of Ba combined or not with gluconate calcium and sodium citrate showed the deposition of metal in tissue such as muscle, bone and blood precipitated. When the Ba was administered together with citrate, there was a significant increase in total deposition of Ba in the body, and the metal was found predominantly in the bones. The treatment with Ba combined with gluconate decreased the total accumulation of this metal in the body, but also favored the deposition in the bones. These compounds helped to soften the deposition of Ba in the muscle and blood precipitated regarding the administration with only Ba. This study showed the contamination of Ba in PN and some medicines from the packaging that it store. Since the sodium citrate, used in many drugs, contributing to a greater absorption in the body. The severity of this is due to the large potential toxicity of Ba direct way in which this metal is administrated in debilitated patients.